PENGARUH EFEKTIFITAS PEMBERIAN VITAMIN C DAN KAFEIN TERHADAP TINGKAT KELELAHAN OTOT SAAT MELAKUKAN AKTIVITAS FISIK MAHASISWA STKIP MB - Wulandari, Titis; Hendra, Jhony (Jurnal Sporta Saintika, 2021)
Strenuous physical activity or ball sports can increase oxygen consumption in the body 10-20 times and 100-200 times in muscles. Increased use of oxygen due to increased activity can increase the production of radicals that can affect the performance of muscle activity marked by a decrease in hemoglobin (Hb). The purpose of the study was to determine the effect of effectiveness of vitamin C and caffeine on hemoglobin levels in maximal physical activity (muscle fatigue). The type of research conducted is quasi-experimental research. Sample testing was carried out at the Talang Pantai Soccer Field and hemoglobin levels were tested at Puskesmas 2 Muara Bungo. This study measured hemoglobin levels before and after consuming 90 mg of vitamin C and 90 mg of caffeine after playing soccer for 45 minutes. The data obtained in the form of hemoglobin levels were analyzed statistically by Analysis of Variance (ANOVA) with a test level of 5%. The results showed that there was an effect of hemoglobin between the control group and the treatment group. This is evidenced by the value of Fh= 6.795 with a sig value of 0.13, the alternating hypothesis (H1) is accepted if the sig value is <0.05 because the sig value is 0.13> 0.05, so that the null hypothesis (H0) is rejected, meaning that there is an effect of caffeine administration on hemoglobin between the groups before caffeine administration and after caffeine administration. Meanwhile, the vitamin C test showed that there was an effect of hemoglobin between the control group and the treatment group. This is evidenced by the value of Fh= 0.029 with a sig value of 0.97, the alternating hypothesis (H1) is accepted if the sig value is <0.05 because the sig value is 0.97> 0.05 so the null hypothesis (H0) is rejected, meaning that there is an effect of vitamin C administration. on hemoglobin between groups before administration of caffeine and after administration of vitamin C.